2012
DOI: 10.1890/es12-00251.1
|View full text |Cite
|
Sign up to set email alerts
|

Changing restoration rules: Exotic bivalves interact with residence time and depth to control phytoplankton productivity

Abstract: Citation: Lucas, L. V., and J. K. Thompson. 2012. Changing restoration rules: Exotic bivalves interact with residence time and depth to control phytoplankton productivity. Ecosphere 3(12):117. http://dx.doi.org/10.1890/ES12-00251.1Abstract. Non-native species are a prevalent ecosystem stressor that can interact with other stressors to confound resource management and restoration. We examine how interactions between physical habitat attributes and a particular category of non-native species (invasive bivalves) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 79 publications
2
41
0
Order By: Relevance
“…This finding applies to deep and shallow environments. However, the range of potential D:ND is broader for shallower habitats (Figure 9), likely due to the potentially short time scales for growth, benthic grazing, and diatom sinking in shallow water, the combination of which can result in a particularly broad range of outcomes (Lucas and Thompson, 2012). 2.…”
Section: Discussion Broad Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding applies to deep and shallow environments. However, the range of potential D:ND is broader for shallower habitats (Figure 9), likely due to the potentially short time scales for growth, benthic grazing, and diatom sinking in shallow water, the combination of which can result in a particularly broad range of outcomes (Lucas and Thompson, 2012). 2.…”
Section: Discussion Broad Lessonsmentioning
confidence: 99%
“…The rationale of conducting this generic study in 1D was to first analyze interactions between sinking, grazing, light-limited growth, and vertical transport, isolated from the effects of horizontal transport between deep and shallow habitats. Both channel and shoal environments were examined because previous work (Lucas et al, 2009;Lucas and Thompson, 2012) has revealed that they can function differently. Biological model parameters for the generic runs were guided by values representative of the broader San Francisco Bay but chosen to be relevant to other estuaries as well ( Table 1, Appendix in Supplementary Material).…”
Section: Generic Experimentsmentioning
confidence: 99%
“…Complete (high) exchange is unlikely to support sufficient residence time to build up blooms of plankton. Low exchange may support blooms, but will cause drawdown of nutrients without replenishment, and limit distribution of food to other regions (i.e., open habitat) where it can be used by grazers and predators (Lucas et al 1999a(Lucas et al , 1999b(Lucas et al , 2002Ahearn et al 2006;Doyle 2010;Lucas and Thompson 2012). Polders that support exchange which varies on a lunar tidal scale are likely to support pelagic production and fishes.…”
Section: Exchange and Geomorphologymentioning
confidence: 99%
“…Turbulence affects whether particles will remain suspended and susceptible to transport. Thus, turbulence affects the time plankton remain productive in the photic zone and whether this material will be intercepted by benthic grazers such as clams (Lehman et al 2009;Lucas and Thompson 2012 Sediment supply decreased about 50% since the 19th century, and the fraction of sediment delivered during winter has increased while the fraction delivered during spring has decreased, mimicking discharge patterns.…”
Section: First Flushmentioning
confidence: 99%
“…Similarly, the relationship between flow characteristics such as velocity and turbulence and the production and sedimentation of organicrich particles (phytoplankton, phytodetritus, and detritus) has not been well characterized for Delta environments; a mismatch between production and transport may lead to significant attenuation of this carbon supply to lower Delta food webs (Lucas and Thompson 2012).…”
Section: Information Gapsmentioning
confidence: 99%